Words in dictionaries and history : essays in honour of R.W. McConchie - Timofeeva, Olga; Säily, Tanja; McConchie, R. W. (Roderick W.) (Terminology and lexicography research and practice ;, 2011)
Bringing together fifteen articles by scholars in Europe and North America, this collection aims to represent and advance studies in historical lexis. It highlights the significance of the understanding of dictionary-making and language-making as important socio-cultural phenomena. With its general focus on England and English, the book investigates the reception and development of historical and modern English vocabulary and culture in different periods, social and professional strata, geographical varieties of English, and other national cultures. The volume is based on individual (meta)lexi.